Nurses' experiences and preferences around shift patterns: A scoping review. - Ourega-Zoé Ejebu; Chiara Dall'Ora; Peter Griffiths (PLoS ONE)
Objective To explore the evidence on nurses' experiences and preferences around shift patterns in the international literature. Data sources Electronic databases (CINHAL, MEDLINE and Scopus) were searched to identify primary studies up to April 2021. Methods Papers reporting qualitative or quantitative studies exploring the subjective experience and/or preferences of nurses around shift patterns were considered, with no restrictions on methods, date or setting. Key study features were extracted including setting, design and results. Findings were organised thematically by key features of shift work. Results 30 relevant papers were published between 1993 and 2021. They contained mostly qualitative studies where nurses reflected on their experience and preferences around shift patterns. The studies reported on three major aspects of shift work: shift work per se (i.e. the mere fact of working shift), shift length, and time of shift. Across all three aspects of shift work, nurses strive to deliver high quality of care despite facing intense working conditions, experiencing physical and mental fatigue or exhaustion. Preference for or adaptation to a specific shift pattern is facilitated when nurses are consulted before its implementation or have a certain autonomy to self-roster. Days off work tend to mitigate the adverse effects of working (short, long, early or night) shifts. How shift work and patterns impact on experiences and preferences seems to also vary according to nurses' personal characteristics and circumstances (e.g. age, caring responsibilities, years of experience). Conclusions Shift patterns are often organised in ways that are detrimental to nurses' health and wellbeing, their job performance, and the patient care they provide. Further research should explore the extent to which nurses' preferences are considered when choosing or being imposed shift work patterns. Research should also strive to better describe and address the constraints nurses face when it comes to choice around shift patterns.